Anxiety (DASS21) and the Quality of Life (FertiQol) of Infertile Women Underwent In Vitro Fertilization - Dian Tjahyadi; Bayu Indrayana Irsyad; Ahmad Yogi Pramatirta; Santi Andayani (Majalah Kedokteran Bandung, 2023)
Infertility affects physical and mental health and has various consequences. In vitro fertilization (IVF) is one of the Assisted Reproductive Technology (ART) programs that include several phases, requiring longer time, more patience, and is expensive. This may make women who undergo the ART program to have higher stress level, especially anxiety. This study aimed to determine the relationship between anxiety and quality of life in infertile patients undergoing assisted reproductive technology programs. This was a cross-sectional observational analytic study performed at Aster Fertility Clinic, Dr. Hasan Sadikin General Hospital and Bandung Fertility Center, Limijati Hospital Bandung, Indonesia, from February until April 2020. The analysis was performed using the DASS21 scale and FertiQol count on 27 subjects undergoing the IVF program and 30 control subjects who were pregnant without IVF program. The statistical analyses used to determine the condition of anxiety and the condition of quality of life were the Chi-square and the Mann-Whitney tests, while the relationship between anxiety and quality of life as the main subject was measured using the Spearman correlation test. The anxiety level as measured with the DASS21 instrument in the subject and control groups was 6.2 vs 0.7 with p<0.001. From the analysis of the FertiQol instrument in the subject and control groups, the scores were 79.6 vs. 98.9 for the mind-body domain (p<0.001); 68.8 vs 98.5 for the emotional domain (p < 0.001); 83.2 vs 95.7 for the relational domain (p<0.001); and 77.6 vs 97.6 for the social domain (p<0.001). For the overall FertiQol core domains, the score was 77.3 vs 97.7 (p<0.001). The correlation between anxiety and the FertiQol total core domains were evident from the results of the Spearman correlation test, with an r-value of -0.479 (p<0.001). Therefore, there is a significant negative correlation between anxiety and quality of life.